Effect Of Hidden Wastes In Overall Equipment Effectiveness Calculation - A. Perumal, Puvanasvaran; Yoong, Sai Sieng; Tay, Choo Chuan (Asian Research Publishing Network (ARPN), 2017)
Overall equipment effectiveness (OEE) is commonly used as a scale in industry to indicate the effectiveness of the machine or process. Although it is just a multiplication of three criteria, availability, performance and quality rate, but it reflects the actual situation of the machine or process. OEE is one of the important elements in continuous improvement plan to assist operation team to indicate the scope of improvements. Therefore, it is important to track out all the wastes available in the calculation. However, it is not an easy task to track out wastes correctly. Although six big losses are mentioned in the OEE philosophy but there are wastes that hidden in the OEE percentages and tend to ignored by operation team. This is the obstacle for industry to achieve optimum OEE level. Therefore, the available of hidden wastes should be visualise and easy to detect. Maynard’s operation sequence technique (MOST) is the suitable tool to quantify the hidden wastes in the OEE calculation since hidden wastes are referring to human interaction, movement or action. MOST is a work measurement tool that used to evaluate the manpower performance. Through MOST, a list of work standard can be constructed and used to compare with the hidden wastes. Then, a modified OEE calculation method is developed to enhance traditional OEE calculation in term of visualization of hidden wastes.